When Human Claims Become Rights. The Case of the Right to Truth over “Desaparecidos” - Arianna Jacqmin (Oñati Socio-Legal Series)
This article deals with the birth of the Right to Truth for the families of missing persons. It refers to socio-legal theories about the origins of human rights that deconstruct their moral and philosophical dimension, and place them in the social milieu in which they arise and develop. This theoretical framework helps analyzing the transitional context of Argentina after the dictatorship, where lawyers promoted the Right to Truth, as the best alternative to a missing criminal justice. Through the analysis of legal memories, the article shows how lawyers and activists, by using the seductive human rights rhetoric, were able to attribute legal qualification to a moral aspiration, as they transformed the desire of the victims to know the destiny of all desaparecidos into a new and autonomous right.